Euphorbia factor L3 ameliorates rheumatoid arthritis by suppressing the inflammatory response by targeting Rac family small GTPase 1. Issue 4 (1st April 2022) - Shi, Haojun; Li, Shufeng; Geng, Yun; Fan, Huancai; Zhang, Ruojia; Zhang, Yuang; Pan, Jihong; Song, Guanhua; Ge, Luna; Xie, Tianhua; Wang, Lin
ABSTRACT: Euphorbia factor L3 (EFL3) is extracted from Euphorbia lathyris and is known for its anti-inflammatory properties. This study focused on the potential anti-inflammatory and therapeutic effects of EFL3 on rheumatoid arthritis (RA) using fibroblast-like synoviocytes (FLSs) and arthritis animal models. Functional analysis showed that EFL3 could ameliorate the inflammatory phenotype of FLSs derived from RA patients, as evidenced by the decreases in cell viability, migration, invasion and cytokine production. Luciferase activity, Western blotting and immunofluorescence assays demonstrated that EFL3 inhibited the nuclear translocation of the p65 subunit and the subsequent activation of the nuclear factor kappa-Β (NF-κB) pathway. Furthermore, the therapeutic effects of EFL3 against arthritic progression were evidenced by decreases in joint swelling, arthritis scores, inflammatory factor production, synovial hyperplasia, and bone destruction in collagen-induced arthritis (CIA) and tumor necrosis factor-α (TNF-α) transgenic (TNF-tg) mouse models. Molecular analysis identified Rac family small GTPase 1 (Rac1) as the potential target that was required for EFL3-mediated suppression of the inflammatory RA FLS phenotype. In summary, this study uncovered the therapeutic potential of EFL3 in RA, which suggests its future clinical use. GRAPHICAL ABSTRACT: uf0001